Analysis of stress level and burnout syndrome among physicians of different medical specialties in primary health care - Brankica Marković; Kosana Stanetić; Verica Petrović; Bojan Stanetić (Биомедицинска истраживања, 2019)
Introduction: Burnout syndrome is a common problem among healthcare workers. The aim of the study was to investigate the level of stress, components of burnout syndrome and the most common causes of workplace stress among the physicians working in the Primary Health Care Center Banja Luka, after which the obtained results concerning family physicians and the physicians of other specialties were compared. Methods: The observational study was conducted by interviewing physicians during the period March to May 2018. All employed physicians were provided with the following questionnaires: The socio-demographic questionnaire, the questionnaire for self-assessment of the level of stress, the questionnaire about the most frequent causes of stress at work and the Maslach Burnout Inventory. Results: The study included 211 physicians, out of a total of 246 physicians (127 family physicians and 84 physicians of other specialties) working in the Primary Health Care Center Banja Luka. There was a significantly higher level of stress (p = 0.011), emotional exhaustion (p < 0.001) and depersonalization (p < 0.001) among family physicians compared to the physicians of other specialties. There was a significant difference in the presence of all causes of stress among family physicians, except the stress concerning the patients requiring emergency care. The multivariate logistic regression analysis found that stress was significantly associated with emotional exhaustion in both groups and with personal accomplishment in family physicians. In family physicians, there was a significant association between a high level of depersonalization and personal accomplishment. In physicians of other specialties significant association was found between education and emotional exhaustion as well as personal accomplishment, and between female gender and high level of depersonalization. Conclusion: The level of stress and the burnout syndrome were considerably more present in family physicians compared to physicians of other specialties.
Keywords: stress; burnout syndrome; causes of stress; family physicians; primary health care